Genome-wide association study of increasing suicidal ideation during antidepressant treatment in the GENDEP project - Perroud, N; Uher, R; Ng, M Y M; Guipponi, M; Hauser, J; Henigsberg, N; Maier, W; Mors, O; Gennarelli, M; Rietschel, M; Souery, D; Dernovsek, M Z; et al. (The pharmacogenomics journal, 2012)
Suicidal thoughts during antidepressant treatment have been the focus of several candidate gene association studies. The aim of the present genome-wide association study was to identify additional genetic variants involved in increasing suicidal ideation during escitalopram and nortriptyline treatment. A total of 706 adult participants of European ancestry, treated for major depression with escitalopram or nortriptyline over 12 weeks in the Genome-Based Therapeutic Drugs for Depression (GENDEP) study were genotyped with Illumina Human 610-Quad Beadchips (Illumina, San Diego, CA, USA). A total of 244 subjects experienced an increase in suicidal ideation during follow-up. The genetic marker most significantly associated with increasing suicidality (8.28 × 10 −7 ) was a single-nucleotide polymorphism (SNP; rs11143230) located 30 kb downstream of a gene encoding guanine deaminase ( GDA ) on chromosome 9q21.13. Two suggestive drug-specific associations within KCNIP4 (Kv channel-interacting protein 4; chromosome 4p15.31) and near ELP3 (elongation protein 3 homolog; chromosome 8p21.1) were found in subjects treated with escitalopram. Suggestive drug by gene interactions for two SNPs near structural variants on chromosome 4q12, one SNP in the apolipoprotein O ( APOO ) gene on chromosome Xp22.11 and one on chromosome 11q24.3 were found. The most significant association within a set of 33 candidate genes was in the neurotrophic tyrosine kinase receptor type 2 ( NTRK2 ) gene. Finally, we also found trend for an association within genes previously associated with psychiatric phenotypes indirectly linked to suicidal behavior, that is, GRIP1 , NXPH1 and ANK3 . The results suggest novel pathways involved in increasing suicidal ideation during antidepressant treatment and should help to target treatment to reduce the risk of this dramatic adverse event. Limited power precludes definitive conclusions and replication in larger sample is warranted.